HGF and MET: From Brain Development to Neurological Disorders - Desole, Claudia; Gallo, Simona; Vitacolonna, Annapia; Montarolo, Francesca; Bertolotto, Antonio; Vivien, Denis; Comoglio, Paolo; Crepaldi, Tiziana (Frontiers in Cell and Developmental Biology, 2021)
Hepatocyte growth factor (HGF) and its tyrosine kinase receptor, encoded by the MET cellular proto-oncogene, are expressed in the nervous system from pre-natal development to adult life where are involved in neuronal growth and survival. In this review we highlight, beyond the neurotrophic action, novel roles of HGF-MET in synaptogenesis during post natal brain development and the connection between deregulation of MET expression and developmental disorders such as autism spectrum disorder (ASD). On the pharmacology side HGF induced MET activation exerts beneficial neuroprotective effects also in adulthood, specifically in neurodegenerative disease, and in preclinical models of cerebral ischemia, spinal cord injuries and neurological pathologies. Among those, Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS). HGF is a key factor preventing neuronal death and promoting survival through pro angiogenic, anti inflammatory and immune modulatory mechanisms. Recent evidence suggest that HGF acts on neural stem cells to enhance neuroregeneration. The possible therapeutic application of HGF and HGF mimetics for treatment of neurological disorders is discussed.